Association of pharmacokinetic biomarkers with early immune recovery following HLA-haploidentical hematopoietic cell transplantation - Shen, Guofang; Synold, Timothy W.; Khan, Shanzay; Horne, David A.; Kanakry, Christopher G.; Nakamura, Ryotaro (Frontiers in Immunology, 2025)
BackgroundProphylactic immunosuppressants for graft-versus-host disease (GVHD) in allogeneic hematopoietic cell transplantation (alloHCT), including post-transplant cyclophosphamide (PTCy) and mycophenolate mofetil (MMF), exhibit complex pharmacokinetic profiles. Interindividual variations in pharmacokinetic exposure to these immunosuppressants or their metabolites may interfere with treatment outcomes.MethodA feasibility study (n = 11) was conducted to investigate the pharmacokinetic/pharmacodynamic relationship in patients undergoing HLA-haploidentical alloHCT with standard high-dose PTCy (50 mg·kg−1·day−1 on days +3/+4) combined with MMF and tacrolimus or sirolimus. Blood samples were collected to assess the variability in pharmacokinetic biomarkers, including exposures [areas under the curve (AUCs)] to cyclophosphamide (Cy), carboxycyclophosphamide (cepm), N-dechloroethyl cyclophosphamide (dccy), 4-ketocyclophosphamide (ketocy), mycophenolic acid (MPA), and mycophenolic acid glucuronide (MPAG). Serial dynamic changes in immune cell populations, including regulatory T cells (Tregs), over the first 3 post-transplant weeks were monitored.ResultsA transient reduction in the proliferation (Ki-67+) of activated (HLA-DR+) T cells coincided with Cy treatment. The ratio of Tregs to the CD4+ T-cell population increased in a time-dependent manner within the first 21 days post-transplant. We observed moderate interindividual variability across all pharmacokinetic biomarkers. Serum creatinine and blood urea nitrogen levels positively correlated with exposure to Cy and MMF metabolites, including cepm, MPA, and MPAG. Using correlation analysis, we further confirmed the negative association between pharmacokinetic (PK) biomarkers and lymphocyte count, but not Treg percentage, suggesting that careful optimization of Cy and MMF dosing may have the potential to support immune recovery, although this requires further validation in larger studies.ConclusionThe relationship of pharmacokinetic biomarkers to immune and clinical outcomes warrants further investigation in larger studies but holds promise for personalizing dosing of GVHD prophylaxis to improve patient outcomes after alloHCT.